1997
DOI: 10.1046/j.1365-2435.1997.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource dynamics and plant growth: a self‐assembling model for individuals, populations and communities

Abstract: 1. We describe a new model of plant growth that is general, deterministic, non‐stationary and mechanistic in nature. Its purpose is to investigate the extent to which the morphology and function of the whole plant can be determined by resource acquisition and utilization on the part of its components. 2. The model is a two‐dimensional section, showing the plant in its above‐ and below‐ground environments. The whole plant is represented by a branching structure made up from standard ‘modules’. The behaviour of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The proportional allocation of biomass to roots vs. shoots is fundamental to interactions among plants (Fitter 1994, Robinson 1994, Reynolds and D'Antonio 1996, Colasanti and Hunt 1997, Aerts and Chapin 1999. Among species, plants allocate proportionally more biomass to roots in nutrient-poor and water-poor environments and more biomass to shoots in light-limited environments (Chapin 1980, Ericsson 1995, Aerts 1999.…”
Section: Phenotypic Plasticity In Response To the Abiotic Environmentmentioning
confidence: 99%
“…The proportional allocation of biomass to roots vs. shoots is fundamental to interactions among plants (Fitter 1994, Robinson 1994, Reynolds and D'Antonio 1996, Colasanti and Hunt 1997, Aerts and Chapin 1999. Among species, plants allocate proportionally more biomass to roots in nutrient-poor and water-poor environments and more biomass to shoots in light-limited environments (Chapin 1980, Ericsson 1995, Aerts 1999.…”
Section: Phenotypic Plasticity In Response To the Abiotic Environmentmentioning
confidence: 99%
“…Moreover, when resources are heterogeneously distributed in space, survival of individuals with better access to them will be disproportionately favoured in relation to the neighbouring plants (i.e. asymmetric contest competition; Colasanti and Hunt, 1997). This process will generate spatial patterns of attraction between dead and surviving individuals (Jacquemyn et al, 2010;Raventos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are several lines of evidence that support the concept of autonomous modular response. Simulation models that assume independent resource acquisition and use by modular units closely replicate real plant growth and the dynamics of population and community (Sorrensen-Cothern 1993;Takenaka 1994;Colasanti and Hunt 1997;Colasanti et al 2001;Hunt and Colasanti 2007). Experimental studies have demonstrated that between-branch or between-shoot carbon movement within plants is very limited; i.e., they demonstrated the carbon autonomy of modular units (Watson and Casper 1984;Yamamoto et al 1999;Hasegawa et al 2003;Lacointe et al 2004;Hoch 2005;Volpe et al 2008).…”
Section: Autonomymentioning
confidence: 95%